Issues affecting young people with asthma through the transition period to adult care. (March 2022) - Robinson, Paul D.; Jayasuriya, Geshani; Haggie, Stuart; Uluer, Ahmet Z.; Gaffin, Jonathan M.; Fleming, Louise
Abstract: Asthma is among the most common medical conditions affecting children and young people, with adolescence a recognised period of increased risk, overrepresented in analyses examining recent increasing asthma mortality rates. Asthma may change significantly during this period and management also occurs in the context of patients seeking increased autonomy and self-governance whilst navigating increasing academic and social demands. A number of disease factors can destabilise asthma during adolescence including: increased rates of anaphylaxis, anxiety, depression, obesity, and, in females, an emerging resistance to corticosteroids and the pro-inflammatory effects of oestrogen. Patient factors such as smoking, vaping, poor symptom recognition, treatment non-adherence and variable engagement with health services contribute to difficult to treat asthma. Significant deficiencies in the current approach to transition have been identified by a recent EAACI task force, and subsequent asthma-specific recommendations, published in 2020 provide an important framework moving forward. As with other chronic conditions, effective transition programmes plan ahead, engage with adolescents and their families to identify the patients' management priorities and the current challenges they are experiencing with treatment. Transition needs may vary significantly across asthma patients and for more complex asthma may include dedicated transition clinics involving multidisciplinary care requiring input including, amongst others, allergy and immunology, psychological medicine, respiratory physicians and scientists and nurse specialists. Across different global regions, barriers to treatment may vary but need to be elicited and an individualised approach taken to optimising asthma care which is sustainable within the local adult healthcare system.